Teachers' Understandings, Perspectives, and Experiences of Dyslexia. (November 2016) - Worthy, Jo; DeJulio, Samuel; Svrcek, Natalie; Villarreal, Doris Ann; Derbyshire, Christine; LeeKeenan, Kira; Wiebe, Molly Trinh; Lammert, Catherine; Rubin, Jessica Cira; Salmerón, Cori
Dyslexia policy and practice have been rapidly outpacing research. Due to legislation and media attention, schools are under pressure to attend to dyslexia, but research provides few clear answers about characteristics, identification, or instruction. Most dyslexia research takes place outside literacy education, and teachers' perspectives are heard only when their knowledge is questioned. Our research addresses these gaps with a qualitative study examining perspectives, understandings, and experiences of 32 Texas public school educators regarding dyslexia. Two major themes were evident: First, teachers felt responsible for meeting the needs of all their students, including those identified as dyslexic. Second, participants named barriers that interfered with attempts to support students, including limited information and confusing policies and procedures. This research provides new information about teacher's understandings, experiences, and perspectives concerning dyslexia that goes beyond surveys. This study's literature review provides information about the state of current dyslexia research, including its limitations.